Differences of Endothelial Corneal Cells Morphology in HIV Patients With and Without Dry Eye Disease: Oral Presentation - Observational Study - General practitioner - Tri Rahmawati; Daniel Johosua Siegers; Juan Felix Pangestu (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Dry eye is a multifactorial disease that affects tear production. Furthermore, the secretion of tears is significantly reduced in patients with HIV. This study aimed to determine whether these changes would make differences in the morphology of corneal endothelial cells. Methods : Our research used an analytic observational method with a cross-sectional approach at the Waihaong Health Center in Ambon City and the Ambon Vlissingen Eye Clinic in March 2023. The sample for this study came from 40 HIV-positive patients who had previously been examined by an ophthalmologist and were diagnosed with dry eye syndrome. Chi-Square analyses were conducted to determine differences in corneal endothelial cell morphology (Cell density, coefficient of variation, hexagonal cells). Results : This study showed that of the 80 eyes of people living with HIV examined, 43,8% had dry eyes. No abnormal hexagonality was found in the corneal endothelial cells in all eyes examined. Decreased endothelial cell density was found in only four eye (5%). Although no significant difference was found for the coefficient of variation of corneal endothelial cells between dry eyes and those without (p=0.764), this study showed that the percentage of coefficient of variation of corneal endothelial cells that were increased/abnormal was higher in dry eye conditions (34.3%) compared to non-dry eyes (31.1%). Conclusion : This study showed no significant differences in the morphology of the corneal endothelial cells of HIV patients with dry eyes. Further research is required with a larger sample size.